Functionalized Cu‐MOF@CNT Hybrid: Synthesis, Crystal Structure and Applicability in Supercapacitors. Issue 20 (8th July 2019) - Ansari, Shagufi Naz; Saraf, Mohit; Gupta, Anoop K.; Mobin, Shaikh M.
Abstract: The synthesis of a metal–organic framework (MOF) namedIITI‐1 is reported by employing an H2 L linker with Cu(NO3 )2 ⋅3 H2 O in a mixed solvent system of N, N ‐dimethyl formamide (DMF) and H2 O. Further, in order to explore the energy storage application ofIITI‐1, aIITI‐1/CNT hybrid was prepared by a simple ultrasonication technique. Incorporation of a carbon nanotube (CNT) in the layeredIITI‐1 MOF gave rise to enhanced electrolyte accessibility along with improved electrochemical storage capacity. The electrochemical investigations reveal a high specific capacitance (380 F g −1 at 1.6 A g −1 ) with a good rate performance forIITI‐1/CNT . TheIITI‐1 MOF and theIITI‐1/CNT composite were characterized by PXRD, BET, SEM, and TEM techniques. Moreover, IITI‐1 MOF was also confirmed by single‐crystal XRD analysis. Abstract : Layer by layer : A functionalized layered copper metal–organic framework (Cu‐MOF) has been synthesized in a facile manner. Incorporation of carbon nanotubes in this layered MOF led to synergistically improved electrochemical energy storage efficiency.